Arthroscopic Meniscopexy for the Treatment of Nontraumatic Osteochondritis Dissecans in the Knee Joint of Adult Patients. (October 2020) - Blanke, Fabian; Feitenhansl, Andreas; Haenle, Maximilian; Vogt, Stephan
Objective: The etiology of osteochondritis dissecans (OCD) is still uncertain. Recently, it has been hypothesized that instability of the anterior horn of the meniscus is an important cause for the development of a nontraumatic OCD in adolescents with good results after surgical stabilization. This case series aims to evaluate the treatment results after meniscus stabilization in adults with nontraumatic OCD. Design: Ten patients with magnetic resonance imaging (MRI)-confirmed OCD of the knee joint, meniscal instability, and closed epiphyseal plates were enrolled in this study. The instable meniscus was stabilized by direct suturing of the anterior horn of the meniscus. MRI examinations were performed preoperative and 6 and 12 months postoperative. The OCD was classified arthroscopically according to Guhl and according to Hughes in the MRI. The overall knee function was evaluated by the Lysholm score before treatment and 12 months postoperative. Results: Four women and 6 men with a mean age of 20.6 ± 1.9 years were included in this study. Preoperatively 60% of the patients showed a grade II or III lesion arthroscopically and 70% a grade III or IVa lesion in the MRI examination. After arthroscopic meniscus stabilization the Lysholm score increased in average from 48.1 ± 14.12 before treatment to 97.5 ± 3.1 postoperative. At final follow-up after 12 months, an improvement of the OCD in the MRI could be demonstrated in all patients (100%). In 80% of the patients a complete healing of the OCD could be noted. Conclusion: The clinical concept of an instable anterior horn of the meniscus as a cause for the development of a nontraumatic OCD seems to be transferable to adults and arthroscopic stabilization can lead to a sufficient healing of this knee pathology.